2020
DOI: 10.1038/s41598-020-71238-w
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic suspended particulate matter as source of eDNA for fish metabarcoding

Abstract: The use of environmental DNA (eDNA) for monitoring aquatic macrofauna allows the non-invasive species determination and measurement of their DNA abundance and typically involves the analysis of eDNA captured from water samples. In this proof-of-concept study, we focused on the novel use of eDNA extracted from archived suspended particulate matter (SPM) for identifying fish species using metabarcoding, which benefits from the prospect of retrospective monitoring and also analysis of fish communities through tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Protocol efficacy can vary significantly in response to local environmental conditions (Piggott, 2016). For example, eDNA in water that has high concentrations of suspended particulates is often bound to particles and more resistant to degradation (Alvarez et al, 1998), resulting in higher eDNA yields (Diaz et al, 2020). However, these same environments often contain high levels of compounds such as humic acid and tannins that inhibit PCR (Albers et al, 2013;McKee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Protocol efficacy can vary significantly in response to local environmental conditions (Piggott, 2016). For example, eDNA in water that has high concentrations of suspended particulates is often bound to particles and more resistant to degradation (Alvarez et al, 1998), resulting in higher eDNA yields (Diaz et al, 2020). However, these same environments often contain high levels of compounds such as humic acid and tannins that inhibit PCR (Albers et al, 2013;McKee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Turbidity in river-dominated estuaries like the SFE is mainly caused by river inputs of suspended particulate matter and resuspension of bottom sediments that reduce phytoplankton biomass (Cloern 1987). While eDNA can be detected in samples of suspended particulate matter collected in sedimentation boxes in rivers (Díaz et al 2020), it is not clear if eDNA co-occurs with other particulates or is stuck to them. In our experiment, turbidity reduced detection rates and we did not see evidence of eDNA sticking to particulates.…”
Section: Discussionmentioning
confidence: 99%
“…While eDNA can be detected in samples of suspended particulate matter collected in sedimentation boxes in rivers (Díaz et al 2020), it is not clear if eDNA co-occurs with other particulates or is stuck to them. In our experiment, turbidity reduced detection rates and we did not see evidence of eDNA sticking to particulates.…”
Section: Effect Of Suspended Particulate Matter On Filtering and Dete...mentioning
confidence: 99%
“…One observation is that previous studies using eDNA techniques found higher species richness in sediment samples than in paired water column samples (Holman et al, 2019). It has also been reported that suspended particulate materials in aquatic environments were a source of eDNA, which was attached to the particles (Díaz et al, 2020). The higher eDNA levels associated with sediment samples may be caused by particulate matter from organisms settling to the bottom or possibly sticking to sediment particles.…”
Section: Introductionmentioning
confidence: 97%